(untitled) (International relations and international law Journal, 2016)
The basic concepts of the world development and the existing energy-ecological situation, which appeared as a result of the globalization of environmental problems and which are some of the main factors of international relations require from the world community urgent decisions. It is known that energy and environment issues that have considering repeatedly on the agenda of international tribunes and scale concepts of sustainable development demand clear actions and decisions in some areas of international politics. Considering these problems, the President of the Republic of Kazakhstan Nursultan Nazarbayev proposed to create a Global energy strategy at the 62nd session of the UN General Assembly. The main objective of the Global energy strategy is to achieve effective level of satisfying of energy and other natural needs of countries by mid-XXI century and their gradual implementation.